[tex] \frac{1}{2} - \frac{1}{3} = \frac{(3 - 2)}{6} = \frac{1}{6} [/tex]
[tex] \frac{2}{3} - \frac{1}{6} = \frac{(2 \times 2 - 1)}{6} = \frac{3}{6} = \frac{1}{2} [/tex]
[tex] \frac{4}{5} - \frac{1}{10} = \frac{(2 \times 4 - 1)}{10} = \frac{7}{10} [/tex]
[tex] \frac{5}{12} - \frac{5}{18} = \frac{(18 \times 5 - 12 \times 5)}{216} = \\ \frac{90 - 60}{216} = \frac{30}{216} = \frac{5}{36} [/tex]
[tex]2 - \frac{4}{4} = 2 - 1 = 1[/tex]
[tex]3 - \frac{6}{5} = \frac{(5 \times 3 - 6)}{5} = \frac{9}{5} [/tex]